International Arbitration and Its Implications for National Legal Sovereignty - Manswab Mahsen Abdulrahman; Aulia Hafhazah; Wardatul Jannah (ISNU Sumatera Utara, 2026)
International arbitration is a dispute resolution mechanism increasingly used in cross-border legal relations, particularly in the areas of international trade and foreign investment. While international arbitration provides legal certainty and protection for investors, it also has implications for national legal sovereignty, particularly when a country must comply with arbitral awards outside the national judicial system. The interaction between international arbitration and national sovereignty reflects a broader transformation in international economic law, where states are no longer the sole actors determining legal outcomes in cross-border economic relations. Through international arbitration mechanisms, particularly Investor-State Dispute Settlement (ISDS), private investors obtain procedural rights to challenge state measures, creating a complex relationship between investment protection and the regulatory autonomy of states. This development raises fundamental questions regarding the extent to which states can maintain their sovereign authority while participating in global economic governance frameworks. This study aims to analyze the implications of international arbitration on national legal sovereignty by examining the legal framework of international arbitration and the response of the Indonesian legal system to international arbitral awards. The research method used is qualitative research with a normative juridical approach through a literature review of laws and regulations, international treaties, and related legal literature. The results indicate that international arbitration has the potential to limit state authority in establishing public policy, but still plays an important role in creating legal certainty and a conducive investment climate. This study argues that the impact of international arbitration on sovereignty should not be understood merely as a reduction of state authority, but as a transformation of sovereignty within an interconnected international legal order. Therefore, the effectiveness of national sovereignty depends on the ability of states to formulate adaptive regulations, negotiate balanced international agreements, and develop institutional capacity to participate effectively in international arbitration proceedings. Therefore, a strategy is needed to strengthen national legal sovereignty through regulatory reform, a consistent role for national courts, and increased institutional capacity so that the state can safeguard national interests without neglecting international legal commitments.